Maturation of Nile-Tilapia (Oreochromis niloticus) Oocytes With Exposed by Goat Inhibin Isolated from Granulose Cells - Linggi, Yulianus; A, Aulanniam; Risjani, Yenni; N. Siregar, Tongku (Jurnal Kedokteran Hewan, 2007)
The present study aimed to investigate the role of inhibin in the regulation of oocytesmaturation. Inhibin was isolated from goat granulose cells and injected by intraperitoneal in to femaleNile-Tilapia. Three days later its gonad was taken by decapitation and the change of oocyte was evaluatedunder microscope. Results showed that average of percentages of oocytes that undergo maturated after exposed with inhibin of 0, 20, 40, and 60g/individual 50.05, 29.44, 21.46, and 30.83%, respectively.The exposure of doses of goat inhibin in Nile-Tilapia showed significantly different (P0.01) to percentages of mature oocytes. It was conluded that exposition of goat inhibin from granulose cells caninducing the maturation of Nile-Tilapia oocytes.Keywords: inhibin, maturation, oocytes